2001
DOI: 10.5367/000000001101297847
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife-Based Tourism and Increased Support for Nature Conservation Financially and otherwise: Evidence from Sea Turtle Ecotourism at Mon Repos

Abstract: The arguments of most conservationists supporting ecotourism have been based on the view that it is environmentally friendly as a resource-use and that receipts from it can counter demands to use the natural resources involved for more extractive economic purposes. But wildlife-based ecotourism can also have positive impacts in itself on the willingness of tourists to pay for wildlife conservation, strengthen the pro-conservation attitudes of tourists, and foster personal actions by them that contribute to wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 5 publications
3
56
2
Order By: Relevance
“…The reason for this is probably the uniqueness of each species and the differences in the likelihood of seeing a particular species. In contrast to findings mentioned in the literature review Tsi et al 2008;Aziz et al 2010), this research does not confirm that income influences willingness to pay, and therefore this study does not clearly support research by Tisdell and Wilson (2001), Tsi et al (2008) and Aziz et al (2010). In terms of age, the results are inconclusive.…”
Section: Findings and Implicationscontrasting
confidence: 56%
See 2 more Smart Citations
“…The reason for this is probably the uniqueness of each species and the differences in the likelihood of seeing a particular species. In contrast to findings mentioned in the literature review Tsi et al 2008;Aziz et al 2010), this research does not confirm that income influences willingness to pay, and therefore this study does not clearly support research by Tisdell and Wilson (2001), Tsi et al (2008) and Aziz et al (2010). In terms of age, the results are inconclusive.…”
Section: Findings and Implicationscontrasting
confidence: 56%
“…These and several other studies do not, however, address the question raised by this research. The only similar studies are those by Hadkler, Sharma, David and Muraleedharan (1997), Tsi et al (2008), Aziz et al (2010), Tisdell and Wilson (2001), and Wilson and Tisdell (2001). However, of these studies, it was only Tisdell and Wilson (2001) who did research on marine species, namely sea turtles.…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, Woehr and Cavell (1993) used it to predict the test score in an introductory psychology class. In tourism, there are several examples of studies using MR. Tisdell and Wilson (2000) used this method to identify several factors that had influenced WTP among visitors to a conservation programme for sea turtles in Mon Repos, Australia. In this study, the qualification of education was found to be the most important factor, followed by income and donations contributed towards conservation.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, studies linking improved environmental behavior, or higher willingness to pay for environmental preservation with education, knowledge, environmental awareness and prior experience are well established in the environmental economics literature (cf. Tisdell and Wilson, 2001). This may be explained by the unavailability of quality survey data, although the concept itself may not be new to researchers in environmental economics.…”
Section: Overview Of the Literaturementioning
confidence: 99%